Formulasi dan evaluasi granul effervescent ekstrak daun binahong (Anredera cordifolia (Tenore) Steen.) - Rahmawati, Indah Fortuna; Pribadi, Prasojo; Hidayat, Imron Wahyu (Pharmaciana, 2016)
The purpose of this research are to find out whether the formulation of effervescent granules from binahong leaves extract has met the standards for effervescent granules and determine the best formulation of effervescent granules. This research is descriptive experimental with data collection from evaluation of effervescent granules. To be able to make effervescent granules, extraction of binahong leaves must be made first. The extracts resulted from a maseration method with 70% ethanol. The effervescent granules formulation were made by 3 design based on their concentration F1 7.4%; F2 14.8%; and F3 22.2%. Effervescent granules of binahong leaves extract are prepared by using wet granulation method. Several physical tests were carried out on the results of effervescent granules of binahong leaves, including organoleptic test, moisture content test, pour volume test, volume of shringkage test, flow capacity test, dispersion test, and pH. The test results showed that all the effervescent granules of binahong leaves (Anredera cordifolia (Tenore) Steen.) have met the standard requirements as good granules. The third formula became the best formulation, With the best value in moisture content test, volume of shringkage test, flow capacity test, and pH.